Pertumbuhan rumput laut Kappaphycus alvarezii yang menggunakan tali ris senar secara vertikultur - Tindage, Tantri W.; Ngangi, Edwin L. A.; Kreckhoff, Reni L.; Mudeng, Joppy D.; Sambali, Hariyani (e-Journal BUDIDAYA PERAIRAN, 2022)
The purpose of the study was to determine the growth of Kappaphycus alvarezii seaweed which was cultivated vertically using strings. The method is the use of the longline method vertically using strings. The experimental design was a completely randomized design with 3 treatments, namely different depths, and each treatment carried out 20 repetitions. Cultivation was carried out for 45 days, where seaweed growth measurements were carried out every 14 days. The highest absolute growth was in treatment A (2,675 grams) followed by treatment B (2,660 grams), treatment C (2480 grams). The highest daily growth rate was treatment B (6.79%) followed by treatment A (6.77%) and treatment C (6.55%). Furthermore, the results of the analysis showed that the absolute growth in treatments A and B was different from treatment C, as well as the daily growth rate which gave a very significant effect, where treatments A and B were very different from treatment C.